Age effects in monetary valuation of mortality risks : The relevance of individual risk exposure - Andrea M. Leiter (University of Innsbruck, Department of Public Finance, 2008)
It is still an ongoing discussion whether benefits resulting from reduced mortality risk should be valuated differently, depending on the age of the beneficiaries. Theory suggests that the influence of age on the value of statistical life (VSL), which is a monetary measure for reduced/prevented mortality risks, is ambiguous. Evidence from empirical studies leads to the same conclusion. The findings in this paper suggest that age becomes effective via age-dependent hazard rates. If a particular risk affects all individuals regardless of their age VSL is rather constant for differently aged people. These results may provide an explanation for the various outcomes in empirical studies.
Keywords: D81; J17; Q26; 330; contingent valuation; risk prevention; age effects; value of statistical life; risk exposure; Sterblichkeit; Willingness to pay; Risikopräferenz; Altersgruppe; Tirol; Österreich